2020
DOI: 10.21037/acs-2020-surd-33
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless and rapid deployment implantation in bicuspid aortic valve: results from the sutureless and rapid-deployment aortic valve replacement international registry

Abstract: Background: Benefits of sutureless and rapid deployment (SURD) bioprostheses in bicuspid aortic valves (BAV) are controversial. The aim of this study is to report the outcomes of patients undergoing aortic valve replacement (AVR) for BAV from the Sutureless and Rapid-Deployment Aortic Valve Replacement International Registry (SURD-IR). Methods: Of the 4,636 patients who received primary isolated SURD-AVR between 2007 and 2018, 191 (4.1%) BAV patients underwent AVR with SURD valve. Results: Overall 30-day morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 16 publications
4
36
1
Order By: Relevance
“…In recent years, however, it has been demonstrated that a Perceval SB can be deployed safely in patients with stenotic BAV without increasing the risk of paravalvular leaks, and that BAV should not be currently considered only a relative contraindication to AVR with SB [ 58 ]. This has also been confirmed by the data from an international registry demonstrating that the implantation of either an SB or RDB in BAV is more technically demanding but not a contraindication, per se, to the use of such devices [ 59 ]. However, important prerequisites for success have been recognized in a detailed analysis of aortic root geometry and with some technical details, particularly the correct decalcification of the aortic annulus and proper sizing [ 59 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In recent years, however, it has been demonstrated that a Perceval SB can be deployed safely in patients with stenotic BAV without increasing the risk of paravalvular leaks, and that BAV should not be currently considered only a relative contraindication to AVR with SB [ 58 ]. This has also been confirmed by the data from an international registry demonstrating that the implantation of either an SB or RDB in BAV is more technically demanding but not a contraindication, per se, to the use of such devices [ 59 ]. However, important prerequisites for success have been recognized in a detailed analysis of aortic root geometry and with some technical details, particularly the correct decalcification of the aortic annulus and proper sizing [ 59 ].…”
Section: Discussionmentioning
confidence: 65%
“…This has also been confirmed by the data from an international registry demonstrating that the implantation of either an SB or RDB in BAV is more technically demanding but not a contraindication, per se, to the use of such devices [ 59 ]. However, important prerequisites for success have been recognized in a detailed analysis of aortic root geometry and with some technical details, particularly the correct decalcification of the aortic annulus and proper sizing [ 59 ].…”
Section: Discussionmentioning
confidence: 65%
“…We believe that it is essential to understand the complexity of the anatomy of the bicuspid aortic valve (BAV) and restore the annular circumference for complete results. 6,21 To reduce PVL incidence, Andreas et al 22 reported the application of an extra stitch in the noncoronary sinus in selected patients, and they did not implant this particular type of valve in patients with extensive calcifications of the root with rigid sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] However, studies reporting this prosthetic valve have vague cases and recommendations. 6,7 The complications of this prosthetic valve include prosthetic valve regurgitation and arrhythmias, for example, in the complete atrioventricular block or left bundle branch block. We rarely have patients who experience hemolytic anemias and heart failure due to prosthetic valve regurgitation.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that it is essential to understand the complexity of the anatomy of bicuspid aortic valve (BAV) and restore the annular circumference for complete results. 6,22 To reduce PVL incidence, Andreas et al 23 reported the application ofan extra stitch in the noncoronary sinus in selected patients, and they did not implant this particular type of valve in patients with extensive calcifications of the root with rigid sinuses. Furthermore, SURD-IR data collection for more than 12 years showed that the incidence (17.8% to 2.7%)(Figure 1)and severity (severe AR 0.6% to 0, moderate AR 3.1% to 1.1%, and mild AR.…”
Section: Discussionmentioning
confidence: 99%